Receptor for advanced glycation end-product (RAGE) gene polymorphism 2245G/A is associated with pro-inflammatory, oxidative-glycation markers and sRAGE in diabetic retinopathy - Ng, Z.X.; Kuppusamy, U.R.; Iqbal, T.; Chua, K.H. (2013)
Background: Receptor for advanced glycation end-product (RAGE) gene polymorphism 2245G/A is associated with diabetic retinopathy (DR). However, the mechanism on how it affects the disease development is still unclear. Aim: This study aims to investigate the relationship between 2245G/A RAGE gene polymorphism and selected pro-inflammatory, oxidative-glycation markers in DR patients. Methods: A total of 371 unrelated type 2 diabetic patients 200 with retinopathy, 171 without retinopathy (DNR) and 235 healthy subjects were recruited. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism method followed by DNA sequencing. The nuclear and cytosolic extracts from peripheral blood mononuclear cells were used for nuclear factor kappa B (NF-kappa B) p65 and superoxide dismutase activity measurement respectively. Plasma was used for glutathione peroxidase activity, advanced oxidation protein product (AOPP), monocyte chemoattractant protein (MCP)-1, pentosidine and soluble RAGE (sRAGE) measurements. Results: DR patients with 2245GA genotype had significantly elevated levels of activated NF-kappa B p65, plasma MCP-1, AOPP and pentosidine but lower level of sRAGE when compared to DR patients with wild-type 2245GG. Conclusion: The RAGE gene polymorphism 2245G/A is associated with pro-inflammatory, oxidative-glycation markers and circulating sRAGE in DR patients. Patients with 2245GA RAGE genotype could aggravate DR possibly via NF-kappa B mediated inflammatory pathway. (C) 2013 Elsevier B.V. All rights reserved.